PEMAHAMAN LAPORAN KEUANGAN BAGI DIASPORA INDONESIA - Henny Wirianata; Elsa Imelda; Hendro Lukman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
Financial reports have important benefits for business, especially among small and medium businesses. However, because their educational background does not touch on economics and business, many small and medium scale entrepreneurs (MSMEs) are unable to produce proper financial reports. However, this can cause MSME owners to make inappropriate decisions due to a lack of information and can also hinder MSME owners if they want to develop their business. For example, to apply for a loan from a bank, it is now mandatory to attach a financial report. This obstacle can be made easier by the many applications provided on the market. The applications offered range from cashiers to financial reporting. MSMEs have started to increase a lot along with the outbreak of the Covid-19 pandemic in 2020-2022. Many Indonesian citizens abroad (diaspora), particularly in Australia, have also experienced the effects of Covid-19. They started looking for other income, by developing their respective businesses. Most of them take the culinary field, but some are in the beauty and laundry fields. The community service activity this time aims to increase the awareness of business actors for the Indonesian citizen diaspora in Australia on understanding the importance of financial reports. In addition, it also provides brief guidelines for the use of several applications that are easy to find in cyberspace. This activity helps them to be able to make the right decisions based on clear financial report information. ABSTRAK Laporan keuanganÂ memiliki manfaat yang penting bagi bisnis khususnya juga di kalangan usaha kecil menengah. Namun karena latar belakang pendidikan yang tidak menyentuh bagian ekonomi dan bisnis, banyak dari pengusaha skala kecil dan menengah (UMKM) tidak mampu membuat laporan keuangan yang layak. Namun hal ini dapat menyebabkan pemilik UMKM mengambil keputusan yang tidak tepat karena kurangnya informasi dan dapat juga menghambat para UMKM jika ingin mengembangkan usahanya. Misalnya untuk pengajuan dana pinjaman dari perbankan, sekarang wajib melampirkan laporan keuangan. Kendala ini dapat dipermudah dengan aplikasi yang banyak disediakan di pasaran. Aplikasi yang ditawarkan mulai dari di kasir hingga pelaporan keuangan. UMKM mulai banyak meningkat seiring dengan mewabahnya pandemi Covid-19 pada 2020-2022. Banyak warga negara Indonesia di luar negeri (diaspora), khususnya di Australia, juga mengalami dampak akibat Covid-19. Mereka mulai mencari penghasilan lainnya, dengan mengembangkan usaha masing-masing. Sebagian besar mengambil bidangÂ kuliner, namun ada juga yang bidang kecantikan dan laundry. Kegiatan pengabdian kepada masyarakat kali ini bertujuan meningkatkan kesadaran para pelaku usaha bagi diaspora WNI di Australia atas pemahaman pentingnya laporan keuangan. Selain itu juga memberikan pedoman singkat pemakaian beberapa aplikasi yang mudah ditemui di dunia maya.Â Kegiatan ini membantu mereka untuk dapat mengambil keputusan yang tepat berdasarkan informasi laporan keuangan yang jelas